Community health workers for non-communicable diseases prevention and control in Bangladesh: a qualitative study - Lal Rawal; Shamim Jubayer; Sohel R. Choudhury; Sheikh Mohammed Shariful Islam; Abu S. Abdullah (BMC, 2020)
Abstract Background The increasing burden of Non-Communicable Diseases (NCDs) in Bangladesh underscores the importance of strengthening primary health care systems. In this study, we examined the barriers and facilitators to engaging Community Health Workers (CHWs) for NCDs prevention and control in Bangladesh. Methods We used multipronged approaches, including a. Situation analyses using a literature review, key personnel and stakeholders' consultative meetings, and exploratory studies. A grounded theory approach was used for qualitative data collection from health facilities across three districts in Bangladesh. We conducted in-depth interviews with CHWs (Health Inspector; Community Health Care Provider; Health Assistant and Health Supervisor) (n = 4); key informant interviews with central level health policymakers/ managers (n = 15) and focus group discussions with CHWs (4 FGDs; total n = 29). Participants in a stakeholder consultative meeting included members from the government (n = 4), non-government organisations (n = 2), private sector (n = 1) and universities (n = 2). Coding of the qualitative data and identification of themes from the transcripts were carried out and thematic approach was used for data analyses. Results The CHWs in Bangladesh deliver a wide range of public health programs. They also provide several NCDs specific services, including screening, provisional diagnosis, and health education and counselling for common NCDs, dispensing basic medications, and referral to relevant health facilities. These services are being delivered from the sub-district health facility, community clinics and urban health clinics. The participants identified key challenges and barriers, which include lack of NCD specific guidelines, inadequate training, excessive workload, inadequate systems-level support, and lack of logistics supplies and drugs. Yet, the facilitating factors to engaging CHWs included government commitment and program priority, development of NCD related policies and strategies, establishment of NCD corners, community support systems, social recognition of health care staff and their motivation. Conclusion Engaging CHWs has been a key driver to NCDs services delivery in Bangladesh. However, there is a need for building capacity of CHWs, maximizing CHWs engagement to NCD services delivery, facilitating systems-level support and strengthening partnerships with non-state sectors would be effective in prevention and control efforts of NCDs in Bangladesh.